Kerjasama Mahasiswa dalam Pembelajaran Kooperatif Tipe Jigsaw pada Mata Kuliah Pengantar Aljabar - Indah Tri Septiani; Abd Qohar (Didaktik Matematika, 2020)
The lecture on algebra has not involved students in working together. Thus, one effort that can be done is implementing the jigsaw cooperative learning model. This study aims to describe the student collaboration activities in the introduction to algebra course using the jigsaw cooperative learning. This research is a quantitative descriptive study. The subjects were 32 first semester students of 2019 who were enrolled in the introduction to algebra course in the Mathematics Education Study Program, FMIPA, Universitas Negeri Malang. The instrument in this study was an observation sheet of student activities, and the supporting data were the results of individual exercises. Data were analyzed descriptively. The results showed that student collaboration activities in the jigsaw cooperative learning in the introduction to algebra course were very good, as indicated by the average score of students in completing individual exercise problems was 90. Thus, it can be concluded that the selection of an appropriate learning model can enhance student collaboration in learning abstract mathematical concepts.